A Simple Experimental Model to Investigate Force Range for Membrane Nanotube Formation - Lor, Chai; Lopes, Joseph D.; Mattson-Hoss, Michelle K.; Xu, Jing; Hirst, Linda S. (Frontiers in Materials, 2016)
The presence of membrane tubules in living cells is essential to many biological processes. In cells, one mechanism to form nano-sized lipid tubules is via molecular motor induced bilayer extraction. In this paper, we describe a simple experimental model to investigate the forces required for lipid tube formation using kinesin motors anchored to 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) vesicles. Previous related studies have used molecular motors actively pulling on the membrane to extract a nanotube. Here we invert the system geometry; molecular motors are used as static anchors linking DOPC vesicles to a two-dimensional microtubule network, and an external flow is introduced to generate nanotubes facilitated by the drag force. We find that a drag force of approximately ≈7 pN is sufficient for tubule extraction for vesicles ranging from 1-2 um in radius. By our method, we find that the force generated by a single molecular motor is sufficient for membrane tubule extraction from a spherical lipid vesicle.